PERAN MIKORIZA PADA SEMAI BEBERAPA SUMBER BENIH MANGIUM (Acacia mangium Willd.) YANG TUMBUH PADA TANAH KERING - Nur Hidayati; Eny Faridah; Sumardi Sumardi (Jurnal Pemuliaan Tanaman Hutan, 2015)
Plants that have mycorrhizal symbiosis tend to be more resistant to the drought because external hyphae of mycorrhizal will expand the surface of water uptake and it can infiltrate into capillary pores so that water uptake for the host plant need will increase. This study aimed to know the response and adaptation mechanisms of mangium in facing drought stress, to investigate mycorrhizal roles in overcoming drought stress on mangium, and to select the origin of mangium seed source that is tolerant to drought stress. The study used mangium seedlings from four different seed sources and was arranged in split plot pattern of randomized block design, with three factors. The result showed that mangium root infected by mycorrhizal decreased along with increasing level of watering intervals. Mycorrhiza increased height-diameter growth and total biomass of mangium for the entire seed source. Total biomass growth of seven month mangium was significantly influenced by the origin of seed source. The highest total biomass was derived from F-1 Wonogiri (7.14 grams) and followed by Group B (6.82 grams), Group C (6.21 g) and Group A (5.84 g). Adaptation mechanisms of mangium seedlings during drought stress were keeping the water status of the plant, improving plant roots system, and thickening the leaf blades.